Exploring research on educational curriculum: a systematic review using bibliometric analysis - Andi Murniati, Andi Murniati; MFZ, M. Fahli Zatrahadi; Drm, Darmawati; ISQ, Istiqomah (Indonesian Institute for Counseling, Education, and Therapy & Indonesian Counselor Association, 2021)
The educational curriculum is made up of learning materials and activities that are meant to help students learn the knowledge, skills, and values they need to become productive, skilled, and good global citizens. The purpose of this study was to evaluate the most productive authors in terms of publication output, as well as the most cited educational curriculum topics. Scopus data sources are utilized because they are considered suitable for analysis with blibliometrics. As a bibliometric analysis tool, VOSviewer software is used to show the author's network, and keywords. Then, for future theme prediction analysis, utilize Rstudio software. The search was conducted on the keyword education curriculum in 2021. Data was obtained from 437 publication documents. Results showed that the authors wrote most of Anderson P's publications, followed by Ayaz-AlKay S and Barrett M. However, in terms of the highest number of citations, different results were found. The highest-grossing writers of 2021 were O'Connor J and Penney D. As expected, the keywords of the education curriculum will be included in the list of keywords that are still in demand by researchers. A number of anticipated keywords will continue to be in demand in the future. There are themes of human, curriculum, child, student, physical education, COVID-19/SARS-cov-2, and medical. These themes, which could serve as future authors' references to the educational curriculum, can be collaborated on.